Néti néti Meaning and Function of an Enigmatic Phrase in the Gārgya-Ajātaśatru dialogue of Bṛhad Āraṇyaka Upaniṣad II.1 and II.3 - Acharya, Diwakar (Indo-Iranian journal, 2013)
This article argues that it is necessary to recognise Sections II.1 and II.3 of the Bṛhad Āraṇyaka Upaniṣad as one discourse. Since nobody among traditional or modern scholars has paid attention to this structure, many problems have been neither seen nor solved. This article does so, and further, exposes textual problems embedded there and analyses them. In this very discourse the expression néti néti is introduced as an ādeśa. Therefore, this article investigates the meaning and function of this expression there. This article also muses on possible implications of the entire discourse of Gārgya and Ajātaśatru.